Automaticity in Stimulus-Parity Synaesthesia. (October 2017) - Dumbalska, Tsvetomira; White, Rebekah C.; Duta, Mihaela D.; Nation, Kate
Automaticity is a defining characteristic of synaesthesia. Here, we assess for automaticity in stimulus-parity synaesthesia; a subtype that has been documented only 3 times in the literature. Synaesthete R experiences many (nonnumerical) stimuli as being odd or even. She described a toy shape-sorter, which paired odd shapes with even colour slots (and vice versa) and relayed difficulties with the incongruency created by this simple toy. Inspired by this anecdote, we devised a computerised task in which Synaesthete R (and 10 control participants) indicated the location of a target shape, which was presented on a coloured bar. Synaesthete R (but not control participants) was faster to report the location of target shapes presented on colours of congruent synaesthetic parity, relative to target shapes presented on colours of incongruent synaesthetic parity. These results constitute the first objective demonstration as to the automatic nature of associations in stimulus-parity synaesthesia.